A Legal Study of The Crimes of Theft, Extortion, and Theft With Aggrevals in Criminal Responsibility - Herman, Andi; Natsir, Muhammad; Syam, Elvi Susanti; Purwanda, Sunardi; Sabir, Muhammad (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the legal aspects of aggravated theft and the concept of criminal liability under Indonesian criminal law. Aggravated theft, as regulated in Article 363 of the Indonesian Criminal Code (KUHP), involves specific circumstances that increase the severity of the offense and consequently result in heavier punishment. The study examines the elements constituting aggravated theft, the factors considered in the determination of criminal responsibility, and the application of legal principles by courts in relevant cases. Using a normative juridical approach, the research employs a qualitative analysis of legislation, legal theories, and judicial decisions related to aggravated theft. The findings indicate that determining criminal liability in aggravated theft is not only based on the actus reus (the criminal act) but also on the mens rea (the criminal intent) of the offender. Furthermore, the study emphasizes the importance of proportional punishment to ensure fairness and justice in law enforcement. This research contributes to a deeper understanding of how Indonesian criminal law upholds justice in handling aggravated theft cases